MONTENEGRIN PORTALS ON EU INTEGRATION – FACTS WITHOUT CONTEXT - Ružić, Nataša; Lučić, Dejan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Since 2009, European integration has been the most salient theme in all Montengrin media. Depending on the editorial policy, citizens have the opportunity to be informed about the success or failure of Montenegro on its path towards the European Union, the opening of new chapters and closing of old ones, the praise or criticism of the governing structure for the fulfillment or non-fulfillment of certain requirements of the EU in the process of European integration. This paper analyzes the manner of reporting on European integration by Montenegrin web portals RTCG (Radio and Television of Montenegro) and daily newspaper Vijesti, and the impact of editorial policy on media coverage. The research confirms that the Montenegrin portals superficially report on the process of European integration, which is reduced to short information without proper explanation, and the mere transfer of officials’ statements. That way the citizens are left on their own, and who wants to be informed and understand this process has to investigate and find information independently.